PENGARUH SOSIALISASI, PEMAHAMAN PERPAJAKAN, KUALITAS PELAYANAN FISKUS DAN TARIF PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM DI KOTA MAKASSAR - Ilham; Maria Ulfah; Sri Nirmala Sari (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This research wants to know the effect of socialization, understanding of taxation, quality of tax services and knowledge of tax rates on UMKM taxpayers compliance in Makassar City. The research analysis used multiple linear regression techniques with SPSS 23 software. The research using purposive sampling technique to 100 respondents. The results showed that partially the socialization variable had no effect on UMKM taxpayers compliance, the tax understanding variable affected UMKM taxpayers compliance, the tax service quality variable had an effect on UMKM taxpayers compliance and the knowledge variable on tax rates had an effect on UMKM taxpayers compliance in Makassar City. Simultaneously, the socialization variable, knowledge of taxation, quality of tax service and knowledge of tax rates affect the compliance of UMKM taxpayers in Makassar City.